Analisis Pemahaman Konsep Matematika Siswa MTs pada Materi Bangun Ruang Berbasis Etnomatematika Kayangan Api Ditinjau dari Gaya Kognitif - Ulya, Aristya Himatul; Rohim, Abdur; Aini, Khafidhoh Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the mathematical concept comprehension abilities of MTs students on spatial building material based on ethnomathematics in terms of cognitive styles. This research employs a descriptive qualitative approach. The research subjects were selected based on the results of cognitive style questionnaires, namely Field Independent (FI) and Field Dependent (FD). Data collection was conducted through cognitive style questionnaires, concept comprehension tests consisting of six items, and in-depth interviews. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. The research results show that: (1) students with a Field Independent cognitive style are able to meet four indicators of mathematical concept understanding, namely restating a concept, classifying elements based on their properties, providing examples and non-examples, and applying concepts in problem-solving; (2) students with a Field Dependent cognitive style can only meet two indicators, namely restating concepts and classifying elements based on their properties. These findings indicate a difference in understanding mathematical concepts based on students' cognitive styles.